Has the public lost confidence in vaccines because of a vaccine scandal in China. Issue 36 (23rd August 2019) - Han, Bingfeng; Wang, Shuai; Wan, Yongmei; Liu, Jiang; Zhao, Tianshuo; Cui, Jiahao; Zhuang, Hui; Cui, Fuqiang
Abstract: Background: A vaccine manufacturer in China and regulatory authorities have been the focus of widespread outrage due to a vaccine scandal. We conducted a rapid survey during a time of intense mainstream and social media attention to determine whether the public's confidence in vaccines was affected. Methods: We selected 7 cities that were not involved in the scandal as the setting for the survey, which was conducted in August 2018. We used a convenience sampling strategy to select subjects in urban streets and rural villages for a face-to-face questionnaire-based survey. Subjects were asked to describe their levels of confidence on a scale from 0 to 9, in which 0 means no confidence, and 9 means very confident. Respondents were asked to assess confidence for two points in time – recollection of their level of confidence before hearing about the scandal and their level of confidence at the time of the survey. Results: In total, 683 individuals were invited to participate and 591 questionnaires were completed, for a response rate of 86.5%. Among respondents, 86.80% had heard of the vaccine scandal. The most common channel for hearing about the scandal was social media (e.g., WeChat), 40.6% of respondents. Regardless of gender, age, education level, province, town or country, or having children under 15 years old, respondents reported a significant decrease in confidence in domestically-produced vaccines. The mean pre-scandal confidence level recalled by respondents was 6.7, and the mean confidence level at the time of the survey was 3.2. Confidence in vaccine manufacturers, institutes for drug control, and drug supervision authorities decreased from 5.6 to 6.0 before the vaccine scandal to 2.0–3.2 at the time of the survey. Confidence in vaccine manufacturers decreased the most, from 5.6 before the scandal to 2.0; confidence in institutes for drug control decreased from 5.8 before the scandal to 2.6 at the time of the survey. Conclusion: This study demonstrated that public confidence was significantly affected by the vaccine scandal, particularly for vaccine producers and drug regulators. The decline in confidence is a reminder to governments that in order to build public confidence for vaccination, regulators have to reform regulatory practices and manufacturers have to ensure vaccine quality.